Reports of Judgments, Advisory Opinions and Orders/ Receuil des arrets, avis consultatifs et ordonnances, Volume 21 (2024) (International Law E-books Online, Collection 2026, 2025)
This volume contains the decisions rendered by the Tribunal in the year 2024 in English and French: An Advisory Opinion issued in Request for Advisory Opinion submitted by the Commission of Small Island States on Climate Change and International Law , a procedural Order issued in M/T "Heroic Idun" (No. 2) and procedural Orders and an Order on provisional measures in "Zheng He" . Le présent volume contient en français et en anglais les décisions rendues par le Tribunal au cours de l'année 2024 : Un avis consultatif rendu dans Demande d'avis consultatif présentée par la Commission des petits États insulaires sur le changement climatique et le droit international , une ordonnance procédurale rendue dans Navire « Heroic Idun » (No. 2) et une ordonnance procédurale et une ordonnance sur les mesures conservatoires rendues dans « Zheng He » .